Leadership for social justice : promoting equity and excellence through inquiry and reflective practice - Normore, Anthony H. (Emerald Publishing Limited : IAP - Information Age Publishing, 2008)
The purpose of this book series is to promote research on educational leadership for social justice. Specifically, we seek edited volumes, textbooks, and full!length studies focused on research that explores the ways educational leadership preparation and practice can be a means of addressing equity concerns throughout P-20 education.Within this book Leadership for Social Justice: Promoting Equity and Excellence Through Inquiry and Reflective Practice the contributors provide a variety of rich perspectives to the social justice phenomenon from the lens of empirical, historical, narrative, and conceptual designs. These designs reiterate the importance of bridging theory and practice while simultaneously producing significant research and scholarship in the field. Collectively, the authors seek to give voice to empowering, social justice-focused research--an area that continues to garner much interest in the areas of educational leadership research, teaching, and learning. In conjunction with the "theme" of this issue, the chapters offer research from an American perspective and offer suggestions, and implications for the field of educational leadership on both a national and international level. The collection contributes to research, theory and practice in educational and community settings.
Keywords: Social justice.; Leadership.; Education -- Administration -- General.; Educational administration and organization.; elektronické knihy; electronic books